2015
DOI: 10.1159/000434683
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated Gastric Carcinoma: Use of Host Cell Machineries and Somatic Gene Mutations

Abstract: Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) is a distinct subtype of gastric carcinoma, consisting of clonal growth of EBV-infected epithelial cells. Its unique characteristics have been demonstrated by epidemiological, clinical and pathological studies using in situ hybridization for EBV-encoded small RNAs. An oncogenic process for EBVaGC has also been revealed. EBV uses various host-cell machineries, including cell division machinery to propagate clonal virus genomes, DNA-methylation machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 101 publications
(118 reference statements)
2
32
1
6
Order By: Relevance
“…Promoter region hypermethylation in certain genes is frequently seen in EBV-positive GC compared to EBV-negative GC [16, 186]. GC and other most common cancers occur by the genetic and epigenetic changes over an extended period.…”
Section: Methylationmentioning
confidence: 99%
“…Promoter region hypermethylation in certain genes is frequently seen in EBV-positive GC compared to EBV-negative GC [16, 186]. GC and other most common cancers occur by the genetic and epigenetic changes over an extended period.…”
Section: Methylationmentioning
confidence: 99%
“…EBVaGC occurs in the upper and middle stomach in the majority. Fukayama et al indicated the tumor distribution in the stomach, with the proportion that 58% in the cardia, 33% in the body, and 9% in the antrum [20,21]. They also depicted the appearance of EBVaGC as ulcerated or saucer-like, with obvious thickened gastric wall.…”
Section: The Risk Factors Of Gcmentioning
confidence: 99%
“…Recientemente, dados los soportes de la asociación VEB-CG, la nueva clasificación molecular del CG incluye un subtipo denominado CaGVEB (76), del cual se conocen dos tipos histológicos: el carcinoma gás-trico similar al linfoepitelioma o carcinoma gástrico con estroma linfoide (85 % a 95 % de los casos) y el adenocarcinoma (5 % a 15 % de los casos) (77)(78)(79). Se sabe que el CaGVEB se presenta en 2 % a 20 % de la población mundial.…”
Section: Veb Y Cáncer Gástrico (Cg)unclassified
“…Se sabe que el CaGVEB se presenta en 2 % a 20 % de la población mundial. Anualmente se diagnostican de 200 000 a 876 000 casos nuevos de CaGVEB, que causan 69 081 a 90 000 muertes cada año (77,(80)(81)(82)(83). En Colombia, la tasa más alta de mortalidad por CaGVEB se reporta en regiones montañosas y la más baja, en regiones planas; es más frecuente en hombres jóvenes y el subtipo histológico predominante es el adenocarcinoma de tipo difuso (84).…”
Section: Veb Y Cáncer Gástrico (Cg)unclassified